Optimasi Pelaksanaan Proyek Jalan Dengan Earned Value Dan Fast Track - Desi Yasri; Andi Yuliardi; Randhi Saily (Sekolah Tinggi Teknologi Pekanbaru, 2022)
Sei Akar – Bagan Jaya Mayor Rehabilitation Project is located on the Sei Akar – Bagan Jaya road, Indragiri Hilir Regency, Riau Province. Corresponding on the project progress report status up to week 18 or 119 calendar working days, the project has been behind schedules 0.871 % and can lead to project failure. Collaboration of Earned Value Analysis, in time and cost monitoring project performance and Fast-Tracking, in accelerating, overlapping or compressing projects, schedule can be optimized project schedule and prevented from contractual penalties. Earned value analysis forcast additional time for 13 days and cost of Rp. 83.390.308,59 for direct cost, Rp.68.793.391,35 for indirect cost, and Rp.181.614.553,16 for penalties. Implementation of Fast Track in anticipating delays for 13 days, the possibility enclose to Tack Coat activity (42 days) and Asphalt Concrete-Binder Course Work activity (35 days). Both activities have met the rules in the application of fast tracking and have the longest duration. Therefor, has the greatest potential reduction in time.